High-Affinity Anti-VISTA Antibody Protects against Sepsis by Inhibition of T Lymphocyte Apoptosis and Suppression of the Inflammatory Response - Tianzhu Tao; Lulong Bo; Teng Li; Longbao Shi; Hui Zhang; Bo Ye; Yuhai Xu; Qingqing Ma; Xiaoming Deng; Guorong Zhang (Hindawi Limited, 2021)
Background. B7 family members and ligands have been identified as critical checkpoints in orchestrating the immune response during sepsis. V-domain Ig suppressor of T cell activation (VISTA) is a new inhibitory immune checkpoint involved in restraining T cell response. Previous studies demonstrated that VISTA engagement on T cells and myeloid cells could transmit inhibitory signals, resulting in reduced activation and function. The current study was designed to determine the potential therapeutic effects of a high-affinity anti-VISTA antibody (clone MH5A) in a murine model of sepsis. Methods. Polymicrobial sepsis was induced in male C57BL/6 mice via cecal ligation and puncture. Expression profiles of VISTA on T lymphocytes and macrophage were examined at 24 and 72 h postsurgery. The effects of anti-VISTA mAb on the 7-day survival, lymphocyte apoptosis, cytokine expression, bacterial burden, and vital organ damage were determined. Furthermore, the effects of anti-VISTA mAb on CD3+ T cell apoptosis and macrophage activation were determined in vitro. Results. VISTA was substantially expressed on T cells and macrophages in sham-operated mice; septic peritonitis did not induce significant changes in the expression profiles. Treatment with MH5A improved the survival of septic mice, accompanied by reduced lymphocyte apoptosis, decreased cytokine expression, and enhanced bacterial clearance. Engagement of VISTA receptor with MH5A mitigated CD3+ T cell apoptosis cultured from CLP mice and suppressed LPS-induced cytokine production by macrophage in vitro. Conclusion. The present study identified VISTA as a novel immune checkpoint in the regulation of T cell and macrophage response during sepsis. Modulation of the VISTA pathway might offer a promising opportunity in the immunotherapy for sepsis.